Effect of real-time feedback device compared to use or non-use of a checklist performance aid on post-training performance and retention of infant cardiopulmonary resuscitation: A randomized simulation-based trial. (March 2023) - Ghazali, Daniel Aiham; Rousseau, Raphaëlle; Breque, Cyril; Oriot, Denis
Abstract: Introduction: This study aims to determine the best method for achieving optimal performance of pediatric cardiopulmonary resuscitation (CPR) during simulation-based training, whether with or without a performance aid. Methods: In this randomized controlled study, 46 participants performed simulated CPR in pairs on a Resusci Baby QCPR™ mannequin, repeated after four weeks. All participants performed the first simulation without performance aids. For the second simulation, they were randomly assigned to one of three groups with stratification based on status: throughout CPR, Group A (n = 16) was the control group and did not use a performance aid; Group B (n = 16) used the CPR checklist; Group C (n = 14) used real-time visualization of their CPR activity on a feedback device. Overall performance was assessed using the QCPR™. Results: All groups demonstrated improved performance on the second simulation (p < 0.01). Use of the feedback device resulted in better CPR performance than use of the CPR checklist (p = 0.02) or no performance aid (p = 0.04). Additionally, participants thought that the QCPR™ could effectively improve their technical competences. Conclusions: Performance aid based on continuous feedback is helpful in the learning process. The use of the QCPR™, a real-time feedback device, improved the quality of resuscitation during infant CPR simulation-based training.